Improving Inkjet Printed Flexible Angle Sensor Performance by Compression-Tension Sensor Pair Compensation - Türkmen, Dila; Acer Kalafat, Merve (Institute of Electrical and Electronics Engineers (IEEE), 2022)
Accepted and published version of this work can be accessed by  https://doi.org/10.1016/j.sna.2022.113752 .    This paper introduces a new method for improved  integrated angle sensing in the foldable robot joints (hinges), using low-cost inkjet printed sensors and a novel physical intelligence based compensation approach. Silver nanoparticle angle sensors are inkjet printed on a flexible PET substrate as a hinge material and implemented as pairs of compression and tension side folding individuals into a rigid experimental setup. Resulting combined signals improved the individual sensor responses due to their compensating physical characteristics, and gave the far best performances in the existing literature in terms of linearity, sensor life-time, static and cyclic drift, hysteresis and dynamic dependency. Proposed approach is promising for eliminating the major limitations on the printed sensor use in flexible hinges and paving the way to reliable, fully soft and easy-to-fabricate all-integrated foldable robots.